Sand Suspension and Transport During Inundation of a Dutch Barrier Island. Issue 12 (12th December 2018) - Engelstad, A.; Ruessink, B. G.; Hoekstra, P.; van der Vegt, M.
Abstract : Overwash and inundation of barrier islands transport large amounts of sediment landward, which could potentially increase the aggradation of these islands in times of sea level rise. However, not much is known about the detailed processes of sediment suspension and transport during inundation. Here we analyze field data of suspended sediment, water levels, waves, and currents which were collected during five inundation events on a barrier island in the Netherlands. We found that depth‐integrated suspended sand concentrations and cross‐shore sand transport showed high variability during and between inundation events at our location, where 80% of the combined transport from all inundation events was completed before high tide. This is primarily caused by variations in cross‐shore flow velocities which were strongest (up to 1.2 m/s onshore) before high tide. However, episodically high depth‐integrated suspended sand concentrations (defined as >2kg/m 2 ) were observed on infragravity time scales (∼20–200 s), suggesting that the contribution of infragravity waves to the combined bed shear stresses of waves and currents was important. High contributions of infragravity waves to the transport coincided with observed bore‐like wave shapes, which might partly be attributed to higher short waves riding and suspending sediment at the position of the crest. Two transport regimes were thus found to govern the transport during inundation: a flow‐driven regime when flow velocities were high (>0.5 m/s) and the ratio of infragravity wave and current related shields numbers was below 0.11 and an episodic regime when this ratio exceeded 0.11. Key Points: Suspended sand concentrations and transport are highly variable during and between inundation events on a Dutch barrier island Most sand is transported before high tide due to high mean flows Infragravity‐wave bores contribute to suspension and transport